2016
DOI: 10.1161/atvbaha.115.306849
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Intracoronary Near-Infrared Spectroscopy Threshold of Lipid-Rich Plaques That Underlie ST-Segment–Elevation Myocardial Infarction

Abstract: C oronary artery disease accounts for ≈1 in every 6 deaths in the United States, with acute ST-segment-elevation myocardial infarction (STEMI) contributing significantly to the overall morbidity associated with this disease. 1 Postmortem studies in patients dying of myocardial infarction consistently demonstrate that the majority of STEMIs are triggered by rupture of a thin-fibrous cap overlying a lipidrich necrotic core. 2-5Intracoronary near-infrared spectroscopy (NIRS) is a catheter-based imaging modalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Madder et al used NIRS-IVUS to study 20 culprit lesions in patients presented with a STEMI and showed that an increased lipid component (lipid core burden index in a 4-mm segment, LCBI 4 mm > 400) was able to differentiate the culprit from the non-ruptured plaques with a high accuracy (AUC: 0.90) [79]. These findings were echoed in a larger study that demonstrated a sensitivity of 64% and a specificity of 85% for LCBI 4 mm > 400 in identifying culprit lesions that caused STEMI [80]. The same research group replicated the above study in patients who presented with a NSTEMI or unstable angina and showed that larger lipid cores were present in the culprit lesions of these patients as well, but in this setting, LCBI 4 mm > 400 had a lower sensitivity and specificity (63.6% and 94.0% for NSTEMI and 38.5% and 89.8% for culprit lesion causing unstable angina, respectively) [81].…”
Section: Multimodality Imagingmentioning
confidence: 92%
“…Madder et al used NIRS-IVUS to study 20 culprit lesions in patients presented with a STEMI and showed that an increased lipid component (lipid core burden index in a 4-mm segment, LCBI 4 mm > 400) was able to differentiate the culprit from the non-ruptured plaques with a high accuracy (AUC: 0.90) [79]. These findings were echoed in a larger study that demonstrated a sensitivity of 64% and a specificity of 85% for LCBI 4 mm > 400 in identifying culprit lesions that caused STEMI [80]. The same research group replicated the above study in patients who presented with a NSTEMI or unstable angina and showed that larger lipid cores were present in the culprit lesions of these patients as well, but in this setting, LCBI 4 mm > 400 had a lower sensitivity and specificity (63.6% and 94.0% for NSTEMI and 38.5% and 89.8% for culprit lesion causing unstable angina, respectively) [81].…”
Section: Multimodality Imagingmentioning
confidence: 92%
“…Demonstrating more reliable characterization of plaque composition, fused IVUS-NIRS imaging underwent histopathological validation in recent studies [72,73]. For instance, the detection of superficial thinning as the IVUS signature of a fibroatheroma is frequently prevented by the presence of calcification; NIRS can detect lipid regardless of substantial calcification [74]. The improved efficacy of fusion of IVUS and NIRS, compared to their separate use, was also proven by some other IVUS-NIRS studies [74,75].…”
Section: Multimodality Imagingmentioning
confidence: 98%
“…For instance, the detection of superficial thinning as the IVUS signature of a fibroatheroma is frequently prevented by the presence of calcification; NIRS can detect lipid regardless of substantial calcification [74]. The improved efficacy of fusion of IVUS and NIRS, compared to their separate use, was also proven by some other IVUS-NIRS studies [74,75]. Because the culprit lesions in patients with non-ST or ST-elevation myocardial infarction (STEMI) have specific morphological characteristics [76], the IVUS-NIRS application was shown to be capable of accurately differentiating STEMI culprit from non-culprit segments [74,75].…”
Section: Multimodality Imagingmentioning
confidence: 99%
“…86 Studies using NIRS have shown that large lipid content, rather than plaque burden, is associated with thin cap fibroatheroma features. 25,87 Larger lipid core burden has been shown to accurately differentiate between culprit and nonculprit lesion in ST-elevation MI patients 88 and has been associated with higher risk for periprocedural myocardial infarction. 89 Interestingly, combination with IVUS may allow for concomitant appreciation of both plaque structure and composition, 90 comparing favorably with OCT. 87 Despite recent studies linking lipid-rich, NIRS-defined nonculprit plaque presence with a 4-fold risk for adverse events (all-cause mortality, nonfatal ACS, stroke, and unplanned revascularizationexcluding those definitely related to the initial culprit lesion) 91 within the first year of follow-up, it cannot be inferred whether these were actually triggered by the detected vulnerable plaque (thus being amenable to preventive stenting) or by other, not assessed lesions (NIRS was only performed over a vessel segment).…”
Section: Percent Atheroma Volume ≥40%mentioning
confidence: 99%